Effects of Plantar Vibration on Bone and Deep Fascia in a Rat Hindlimb Unloading Model of Disuse - Huang, Yunfei; Fan, Yubo; Salanova, Michele; Yang, Xiao; Sun, Lianwen; Blottner, Dieter (Frontiers in Physiology, 2018)
The deep fascia of the vertebrate body comprises a biomechanically unique connective cell and tissue layer with integrative functions to support global and regional strain, tension, and even muscle force during motion and performance control. However, limited information is available on deep fascia in relation to bone in disuse. We used rat hindlimb unloading as a model of disuse (21 days of hindlimb unloading) to study biomechanical property as well as cell and tissue changes to deep fascia and bone unloading. Rats were randomly divided into three groups (n=8, each): hindlimb unloading (HU), HU + vibration (HUV) and cage-control (CON). The HUV group received local vibration applied to the plantar of both hind paws. Micro-computed tomography analysed decreased bone mineral density (BMD) of vertebra, tibia, and femur in HU vs. CON. Biomechanical parameters (elastic modulus, max stress, yield stress) of spinal and crural fascia in HU were always increased vs. CON. Vibration in HUV only counteracted HU-induced tibia bone loss and crural fascia mechanical changes but failed to show comparable changes in the vertebra and spinal fascia on lumbar back. Tissue and cell morphometry (size and cell nuclear density), immunomarker intensity levels of anti-collagen-I and III, probed on fascia cryosections well correlated with biomechanical changes suggesting crural fascia a prime target for plantar vibration mechano-stimulation in the HU rat. We conclude that the regular biomechanical characteristics as well as tissue and cell properties in crural fascia and quality of tibia bone (BMD) were preserved by local plantar vibration in disuse suggesting common mechanisms in fascia and bone adaptation to local mechanovibration stimulation following hind limb unloading in the HUV rat.